Are Biogenic and Pyrogenic Mesoporous SiO2 Nanoparticles Safe for Normal Cells? - Solarska-Ściuk, Katarzyna; Adach, Kinga; Cyboran-Mikołajczyk, Sylwia; Bonarska-Kujawa, Dorota; Rusak, Agnieszka; Cwynar-Zając, Łucja; Machałowski, Tomasz; Jesionowski, Teofil; Grzywacz, Katarzyna; Fijałkowski, Mateusz (Molecules (Basel, Switzerland), 2021)
Silicon dioxide, in the form of nanoparticles, possesses unique physicochemical properties (size, shape, and a large surface to volume ratio). Therefore, it is one of the most promising materials used in biomedicine. In this paper, we compare the biological effects of both mesoporous silica nanoparticles extracted from Urtica dioica L. and pyrogenic material. Both SEM and TEM investigations confirmed the size range of tested nanoparticles was between 6 and 20 nanometers and their amorphous structure. The cytotoxic activity of the compounds and intracellular ROS were determined in relation to cells HMEC-1 and erythrocytes. The cytotoxic effects of SiO2 NPs were determined after exposure to different concentrations and three periods of incubation. The same effects for endothelial cells were tested under the same range of concentrations but after 2 and 24 h of exposure to erythrocytes. The cell viability was measured using spectrophotometric and fluorimetric assays, and the impact of the nanoparticles on the level of intracellular ROS. The obtained results indicated that bioSiO2 NPs, present higher toxicity than pyrogenic NPs and have a higher influence on ROS production. Mesoporous silica nanoparticles show good hemocompatibility but after a 24 h incubation of erythrocytes with silica, the increase in hemolysis process, the decrease in osmotic resistance of red blood cells, and shape of erythrocytes changed were observed.
Keywords: Silicon Dioxide; cytotoxicity; oxidační stres; Nanoparticles; erytrocyty; poréznost; hemolýza; povrchové vlastnosti; Oxidative Stress; lidé; Reactive Oxygen Species; Endothelial Cells; nanočástice; mesoporous silica; biogenic and pyrogenic silicon dioxide; Porosity; Erythrocytes; endoteliální buňky; oxid křemičitý; reaktivní formy kyslíku; Hemolysis; nanoparticles; Cell Survival; viabilita buněk; Surface Properties; Humans